2008
DOI: 10.1523/jneurosci.2320-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Regulates Axon Behavior through Changes in Microtubule Growth Directionality: A New Role for Adenomatous Polyposis Coli

Abstract: Axon guidance and target-derived signals control axonal behavior by regulating the cytoskeleton through poorly defined mechanisms. In particular, how these signaling molecules regulate the growth and directionality of microtubules is not well understood. Here we examine the effect of Wnts on growth cone remodeling, a process that precedes synapse formation. Time-lapse recordings reveal that Wnt3a rapidly inhibits growth cone translocation while inducing growth cone enlargement. These changes in axonal behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(205 citation statements)
references
References 56 publications
12
186
1
Order By: Relevance
“…5C). Another downstream target of GSK-3␤ is adenomatous polyposis coli (APC), which promotes microtubule assembly at the growth cone when dephosphorylated (Zhou et al, 2004;Koester et al, 2007;Purro et al, 2008). We found that knockdown of APC also suppressed Dock3-mediated axonal outgrowth after BDNF treatment (Fig.…”
Section: Dock3 Induces Phosphorylation Of Gsk-3␤ At the Plasma Membranementioning
confidence: 81%
See 1 more Smart Citation
“…5C). Another downstream target of GSK-3␤ is adenomatous polyposis coli (APC), which promotes microtubule assembly at the growth cone when dephosphorylated (Zhou et al, 2004;Koester et al, 2007;Purro et al, 2008). We found that knockdown of APC also suppressed Dock3-mediated axonal outgrowth after BDNF treatment (Fig.…”
Section: Dock3 Induces Phosphorylation Of Gsk-3␤ At the Plasma Membranementioning
confidence: 81%
“…The importance of CRMPs in axonal formation is highlighted by the evidence that axonal outgrowth is arrested when CRMPs are phosphorylated by some kinases, such as glycogen synthase kinase-3␤ (GSK-3␤), because this phosphorylation causes dissociation of CRMPs from microtubules (Eickholt et al, 2002;Yoshimura et al, 2005). In addition, adenomatous polyposis coli (APC), which promotes microtubule assembly at the growth cone, is another downstream target of GSK-3␤ (Zhou et al, 2004;Koester et al, 2007;Purro et al, 2008), indicating the importance of GSK-3␤ in this dynamic process. In this study, we show that Dock3 binds to GSK-3␤ and inhibits its activity, thereby activating CRMP-2 and APC.…”
Section: Introductionmentioning
confidence: 99%
“…At the roof plate boundary in the zebrafish diencephalon, a Wntexpressing intermediate target for commissural axons, growth cones normally pause and enlarge before crossing. Wnt can regulate axonal microtubules and induce growth cone enlargement via multiple pathways (Gordon-Weeks, 2004;Ciani and Salinas, 2007;Purro et al, 2008;Salinas and Zou, 2008). We suggest that the additive effects of Wnt signaling at the intermediate target and increased microtubule polymerization and stability in phr mutants cause excessive microtubule looping, preventing growth cones from exiting the paused state.…”
Section: Microtubules and Intermediate Targetsmentioning
confidence: 91%
“…It was furthermore demonstrated that the stabilization of microtubules by Dvl-1 is enhanced by GSK3 inhibition [280]. Studies in C. elegans, Drosophila and vertebrates have led to the conclusion that Wnt/ -catenin signaling may regulate the orientation of the mitotic spindle through Dishevelled [281][282][283].…”
Section: Dishevelledmentioning
confidence: 99%